ECO FRIENDLY ARCHITECTURE– A PRELUDE IN THE SULTANATE OF OMAN - Hegazy, Soheir Mohamed (MATTER: International Journal of Science and Technology, 2018)
In developed countries, the issue of green architecture and sustainability practices has been a major concern to building professionals and the community for many years. On the contrary, in the developing countries, the same issues are beyond public awareness. The Sultanate of Oman is one of the countries whose national economy is mainly based on nonrenewable energy resource, oil. In addition, the recent plummet in the price. of fossil fuel ushered Oman to seek alternative energy resources, and to think of adopting new policies. Unprecedented in the Third world, the national competition for Eco House Design was announced. Five examples of Eco Houses were designed and constructed during the first phase. This research aims to shed light on this remarkable Omani experience among the developing countries. The methodology of the research is incumbent on a theoretical foundation of previous related references analysis and a cross comparative case study. Other tools were used like interviews and site visits. The research succeeded in outlining the design criteria of eco-friendly architecture and clarifying the starting point taken by the Oman to adopt the green and issues. In addition, two examples of the Eco-houses in arid zones were provided. In the future, further steps have to be taken to re-direct the Omani society to adopt the green attitude.